Increased plasma genistein after bariatric surgery could promote remission of NAFLD in patients with obesity - Wang, Geng; Wang, Yu; Bai, Jie; Li, Gang; Liu, Yang; Deng, Shichang; Zhou, Rui; Tao, Kaixiong; Xia, Zefeng (Frontiers in Endocrinology, 2023)
Background Bariatric surgery is associated with a positive effect on the progress of non-alcoholic associated fatty liver disease (NAFLD). Although weight loss is the obvious mechanism, there are also weight-independent mechanisms. Methods We collected blood samples from 5 patients with obesity before and 3 months after surgery and performed an LC-MS-based untargeted metabolomics test to detect potential systemic changes. We also constructed sleeve gastrectomy (SG) mice models. The plasma, liver and intestine samples were collected and analyzed by qPCR, ELISA and HPLC. Cohousing experiments and feces transplantation experiments were performed on mice to study the effect of gut microbiota. Genistein administration experiments were used to study the in vivo function of the metabolites. Results Plasma genistein (GE) was identified to be elevated after surgery. Both clinical data and rodent models suggested that plasma GE is negatively related to the degree of NAFLD. We fed diet-induced obese (DIO) mice with GE, and we found that there was significant remission of NAFLD. Both in vivo and in vitro experiments showed that GE could restrict the inflammation state in the liver and thus relieve NAFLD. Finally, we used co-housing experiments to alter the gut microbiota in mice, and it was identified that sleeve gastrectomy (SG) mice had a special gut microbiota phenotype, which could result in higher plasma GE levels. By feces transplantation experiment (FMT), we found that only feces from the SG mice (and not from other lean mice) could induce higher plasma GE levels. Conclusion Our studies showed that SG but not calorie restriction could induce higher plasma GE levels by altering the gut microbiota. This change could promote NAFLD remission. Our study provides new insights into the systemic effects of bariatric surgery. Bariatric surgery could affect remote organs via altered metabolites from the gut microbiota. Our study also identified that additional supplement of GE after surgery could be a therapy for NAFLD.